Ir(III)-Catalyzed Carbocarbation of Alkynes through Undirected Double C-H Bond Activation of Anisoles - Romanov-Michailidis, Fedor (J Am Chem Soc, 2018)
A novel, electron-deficient cyclopentadienyl iridium(III) catalyst enables sequential cleavage of arene C(sp(2))-H and methoxy C(sp(3))-H bonds of anisoles, generating reactive metalacycles that insert difluoroalkynes to afford chromenes under mild reaction conditions. This transformation is an arylalkylation of an alkyne – a carbocarbation – via a non-chelate-assisted cleavage of two C-H bonds.